Business models in Circular Economy concept - Rudnicka, Agata (Research Papers of Wrocław University of Economics, 2018)
It seems that in the 21st century business needs to adapt faster than ever to the expectations of the external environment. This makes it necessary to look for new solutions that give the opportunity to reconcile the needs and expectations of consumers who are increasingly aware and enterprise which are trying to meet new requirements. As a result there is a change in the perception of existing business models and a move beyond the linear economic model. The new optics of looking at business is both legitimate and necessary. One of such concepts is Circular Economy (CE) which incorporates the existing management concepts into the strategic idea of natural resources protection. What is more, the assumptions of the CE are coherent with the postulates of sustainable development and, in particular, environmental aspects, which constitutes its additional value. The aim of the article is to present the idea of CE in terms of business models
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2018; Nr 520; s. 106-114
Keywords: business model; circular economy; circular business models; sustainability; modele biznesowe; biznesowe modele cyrkularne